2020
DOI: 10.20944/preprints202003.0341.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The AI-Discovered Aetiology of COVID-19 and Rationale of the Irinotecan+Etoposide Combination Therapy for Critically Ill COVID-19 Patients

Abstract: We present the AI-discovered aetiology of COVID-19, based on a precise disease model of COVID-19 built under five weeks that best matches the epidemiological characteristics, transmission dynamics, clinical features, and biological properties of COVI D-19 and consistently explains the rapidly expanding COVID-19 literature. We present that COVID-19 implements a unique unbiased survival strategy of balancing viral replication with viral spread by increasing its dependence on (i) ACE2-expressing cells for viral e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 7 publications
(10 reference statements)
1
12
0
Order By: Relevance
“…The decision-support integration of HAI at the stage of selecting development candidates to enter first-in-human studies could significantly increase the average clinical success rate of investigational new drugs from 7.9% 8 to 90.1% for nearly any disease. 9, 10 This result confirms that exponentially extracted knowledge alone may be sufficient to accurately predict clinical success, effecting a complete reversal of Eroom’s law. 4 The trained HAI is also the world’s first clinically validated model of human aging that could substantially speed up the discovery of preventive medicine for all age-related diseases.…”
supporting
confidence: 63%
See 3 more Smart Citations
“…The decision-support integration of HAI at the stage of selecting development candidates to enter first-in-human studies could significantly increase the average clinical success rate of investigational new drugs from 7.9% 8 to 90.1% for nearly any disease. 9, 10 This result confirms that exponentially extracted knowledge alone may be sufficient to accurately predict clinical success, effecting a complete reversal of Eroom’s law. 4 The trained HAI is also the world’s first clinically validated model of human aging that could substantially speed up the discovery of preventive medicine for all age-related diseases.…”
supporting
confidence: 63%
“…No clinical data were available worldwide when the preprint of ABNN’s COVID-19 disease model was published on 20. March 2020 24 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings are consistent with recent studies that propose topoisomerase inhibitors or PI3K/mTOR inhibitors for treatment of COVID-19. One recent study proposed Irinotecan and Etoposide combination therapy for critically ill COVID-19 patients 9 based on the immunomodulatory and viral suppressive profiles of these drugs. Additionally, a recent loss-of-function experiment revealed that certain topoisomerases were required for efficient replication of positive-sense RNA viruses including SARS-CoV-2 10 .…”
Section: Resultsmentioning
confidence: 99%